2001
DOI: 10.1002/1521-4095(200104)13:8<584::aid-adma584>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron Transmission Through “Cascade-Like” Langmuir-Blodgett Films Containing CdS Quantum Particles

Abstract: The electronic properties of hybrid Langmuir–Blodgett (LB) films containing CdS quantum particles (QP) of different size arranged in “cascade like” architectures on gold are studied. The energy distribution of photoelectrons ejected from the gold substrate and transmitted through the LB films is reported. The electronic properties were found to depend on the structure and the organization of the layers relative to the gold substrate, and on the interaction between the metal substrate and the film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…[8][9][10] In addition, NPs have been suggested as a mean of enhancing and controlling electromagnetic field on the nanoscale 11 and hybrid structures of NPs and organic molecules were found to have cooperative electronic properties. 12,13 The InAs/ ZnSe core/shell nanocrystals, used in the current study, were prepared by a two-step process as detailed elsewhere. 14 The outer surface of these nanocrystals is coated by organic ligands which render the particles soluble in organic solvents.…”
mentioning
confidence: 91%
“…[8][9][10] In addition, NPs have been suggested as a mean of enhancing and controlling electromagnetic field on the nanoscale 11 and hybrid structures of NPs and organic molecules were found to have cooperative electronic properties. 12,13 The InAs/ ZnSe core/shell nanocrystals, used in the current study, were prepared by a two-step process as detailed elsewhere. 14 The outer surface of these nanocrystals is coated by organic ligands which render the particles soluble in organic solvents.…”
mentioning
confidence: 91%
“…These results are consistent with former studies that also indicate that the interaction between the substrate and the QPs is very weak when separated via a long spacer. 13,22 Scheme 3 presents the energy levels and the processes involved in the photoattenuated CPD experiments. The change in the CPD signal must result from the hybrid film being charged, either positively or negatively.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Previously, we investigated the electronic properties of these films applying the photoemission technique. 13 The contact potential difference (CPD) technique measures the contact potential between a known surface and that probed by varying the distance between them, hence, varying the electrical capacitance of the system. Therefore, the method is contact free.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that hybrid composite of sulfonated polystyrene (PS) matrix was prepared through in situ CdS nanoparticles growing;4 CdS nanoparticles were incorporated into polyacrylamide hydrogel by swelling and shrink cycles to obtain polymeric composite;5 CdS nanocomposite were fabricated on the different polymer matrix such as polyacrylamide,6 dendrimers,7 polymer micelles,8–10 and layer‐by‐layer polyelectrolyte 11. The organic‐inorganic hybrids Langmuir‐Blodgett films were prepared via topotactic gas‐solid reaction with H 2 S 12,13. At the same time, biomacromolecules have been utilized to fabricate CdS nanocomposites, such as the chaperonin proteins wrapping CdS as high thermal and chemical stability semiconductor nanocrystals,14 porous cellulose fibers also have been employed as an effective nanoreactor as well as particle stabilizer for in situ synthesis of metal nanoparticles from metal precursor solution 15,16.…”
Section: Introductionmentioning
confidence: 99%